Morphological and functional criteria for the effectiveness of recreational activities in children - A. V. Tarakanov; E. V. Chaplygina; E. S. Elizarova; T. D. Tarakanova; O. V. Korshunov (Медицинский вестник Юга России, 2021)
Objective. The study aimed to perform a comprehensive morphofunctional assessment of the effectiveness of recreational activities in children aged 9–12 years in the summer of 2019.Materials and methods. The study was conducted by the “Problem scientific laboratory of physical methods of diagnosis and treatment” of RostGMU in the children’s health and recreation camp “Mir” (Krasnyi Desant village, Gulf of Taganrog). Procedures and time of the study: somatometry, bioimpedance analysis, сardiointervalography, stabilometrics on the 2nd day of stay and 2.5 weeks after. Two groups were formed: Group I included overweight children (OW), n = 15 (boys, n = 9; girls, n = 6); Group II included children with normal physical development (NPD), n = 37 (boys, n = 17; girls, n = 20). The children received a non-drug complex of camp resource provision for 3 weeks.Results. Health measures did not lead to significant changes in the somatometric parameters. According to the results of the сardiointerval recording, an authentic increase in the variational range and vegetative rhythm index was found in children with NPD, which indicates an increase in the parasympathetic activity of regulation. The stress index decreased by 30% in the case of NPD, and by 6% in the case of OW. Data from the stabilometric “Balls” simulator showed that after the recovery, the regulation of postural control was optimized, and decision-making processes were accelerated, especially in children with NPD.Conclusion. The study showed that in order to assess the effectiveness of recreational activities, along with “mandatory” methods, it is advisable to use functional methods such as cardiointervalography and stabilometrics, which can be recommended for use in health and rehabilitation institutions to assess the adaptive capabilities of the organism.